2017
DOI: 10.1016/j.ahj.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of a 1-hour troponin T protocol in suspected acute coronary syndromes: Design of the Rapid Assessment of Possible ACS In the emergency Department with high sensitivity Troponin T (RAPID-TnT) study

Abstract: Demonstrating that a 0/1-hour hs-TnT protocol improves the effectiveness and efficiency of care within a robust comparative study will fill an evidence gap that currently limits the translation of more precise hs-TnT testing into better patient and health service outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Troponin detection exerts a great influence on clinical decision‐making. More sensitive troponin assays have the potential to better evaluate the patients with suspected ACS presenting to the emergency department (ED), allowing for earlier safe discharge of low‐risk chest pain and earlier recognition of AMI . Conventional troponin assays could lead to an inappropriate discharge, while more sensitive troponin assays may result in avoidable diagnostic testing.…”
Section: Introductionmentioning
confidence: 99%
“…Troponin detection exerts a great influence on clinical decision‐making. More sensitive troponin assays have the potential to better evaluate the patients with suspected ACS presenting to the emergency department (ED), allowing for earlier safe discharge of low‐risk chest pain and earlier recognition of AMI . Conventional troponin assays could lead to an inappropriate discharge, while more sensitive troponin assays may result in avoidable diagnostic testing.…”
Section: Introductionmentioning
confidence: 99%
“…All troponin samples were analysed using 5 th generation hs-cTnT assay (Roche Diagnostics: lower limit of quantification: 5ng/L; 99th percentile upper reference limit in a normal population: male = �22ng/L, PLOS ONE female = �14ng/L; lowest concentration with a coefficient of variation <10%: 4.49 ng/L). During the study period, an elevated troponin was only reported to the treating clinician at a hs-cTnT concentration �29ng/L due to previous and ongoing studies [26,27]. A clinically significant rise and/or fall was determined as a relative change of �20% or a gradient of �3ng/L/hr from initial to any subsequent measurement within 24 hours as per expert consensus and existing literature [2,28].…”
Section: Biomarker Measurementsmentioning
confidence: 99%
“…9 Establishing protocols for the incorporation of this assay into current practice and further research assessing its effect on patient care and health care systems will improve the use of hs-cTnT. 10 Editor's Note: This is a clinical synopsis, a regular feature of the Annals' Systematic Review Snapshot (SRS) series. The source for this systematic review snapshot is: Michael Brown, MD, MSc, Jestin N. Carlson, MD, MS, and Alan Jones, MD, serve as editors of the SRS series.…”
Section: Commentarymentioning
confidence: 99%